Is Military Spending Converging Across Countries? : An Examination of Trends and Key Determinants - Clements, Benedict (IMF Working Papers; Working Paper ;, 2019)
This paper studies the evolution of worldwide military spending during 1970-2018. It finds that military spending in relation to GDP is converging, but into three separate groups of countries. In the largest group, responsible for 90 percent of worldwide spending, outlays have remained stubbornly high. Military spending in developing economies reacts to improvements in security conditions and military spending in neighboring countries, suggesting that further increases in the peace dividend are possible. In developing economies, rising social spending tends to crowd out military outlays, but this is not the case in advanced economies. With social outlays projected to rise as developing countries look to achieve the Sustainable Development Goals (SDGs), military spending could come under pressure to fall further.